Microbial Bioremediation Strategies for Degradation of Persistent Organic Pollutants: Synergistic Approach Involving Microbes to Address the Global Concern - Nag, Mayuri; Sarkar, Pritam; Kumar, Saurav (Chronicle of Bioresource Management, 2024)
Persistent organic pollutants (POPs) are synthetic chemicals that do not degrade easily in the environment, resist chemical, biological and photolytic degradation, have a strong affinity towards fats (lipophilic) and can either be absorbed in atmospheric particles or occur in vapor phase. Polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), dioxins, dibenzofurans and polycyclic aromatic hydrocarbons (PAHs) are few examples of POPs. Microbial degradation technology such as bioremediation is emerging as a suitable and cost-effective tool when compared to the traditional technologies for treating POPs. This technique involves three important components: microbe, contaminant and nutrient, forming the bioremediation triangle for degradation of pollutant. This article is a brief description of microbes mediated bioremediation of POPs including bacterial, fungal and algal degradation and enzymes involved in the process.